Tobacco Taxation and Impact of Policy Reforms : Trinidad and Tobago - World Bank Group (World Bank, Washington, DC, 2018)
Evidence from across the world shows that raising taxes sharply on tobacco products, and then adjusting for inflation and increased affordability due to growing incomes, is the single most cost-effective measure to reduce tobacco consumption. A scaled-up and stronger tobacco control effort is required in Trinidad and Tobago to achieve the WHO-recommended target of at least 30 percent reduction in smoking prevalence by 2030, which would avoid ill health, premature mortality, and disability among current and future smokers by the end of the 21st century. The benefits of tobacco taxation go beyond public health. As documented in a recent report by researchers at the International Monetary Fund in many countries, raising tobacco taxes can offer a "win–win": higher revenue and positive health outcomes. While countries' circumstances and governments weighting of revenue, health, and other objectives vary, and hence the desirable level of tobacco tax rates, in many cases, current tax rates are far below what is feasible in terms of revenue potential. In the case of Trinidad and Tobago, increasing tobacco taxes as assessed in this report, could serve revenue purposes as well as health and other objectives. And if the government decides to put more weight on health objectives, it could raise taxes even further.